2015
DOI: 10.1038/srep13222
|View full text |Cite
|
Sign up to set email alerts
|

QIAD assay for quantitating a compound’s efficacy in elimination of toxic Aβ oligomers

Abstract: Strong evidence exists for a central role of amyloid β-protein (Aβ) oligomers in the pathogenesis of Alzheimer’s disease. We have developed a fast, reliable and robust in vitro assay, termed QIAD, to quantify the effect of any compound on the Aβ aggregate size distribution. Applying QIAD, we studied the effect of homotaurine, scyllo-inositol, EGCG, the benzofuran derivative KMS88009, ZAβ3W, the D-enantiomeric peptide D3 and its tandem version D3D3 on Aβ aggregation. The predictive power of the assay for in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 32 publications
2
97
0
3
Order By: Relevance
“…This is not surprising given the fact that the sample huPrP(23-144)-Aβ* contains eight times more Aβ (monomer equivalent) than huPrP(23-144) molecules. Not every monomer within the oligomer (containing 23 monomer units on average 47 ) might be able to bind to huPrP in the same way and have therefore the same conformation 33 , as described above. These non-identical conformers can have different origins: (i) different types of monomers within the oligomer, because not every monomer can bind to huPrP (Aβ-huPrP vs. Aβ-Aβ interactions);…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given the fact that the sample huPrP(23-144)-Aβ* contains eight times more Aβ (monomer equivalent) than huPrP(23-144) molecules. Not every monomer within the oligomer (containing 23 monomer units on average 47 ) might be able to bind to huPrP in the same way and have therefore the same conformation 33 , as described above. These non-identical conformers can have different origins: (i) different types of monomers within the oligomer, because not every monomer can bind to huPrP (Aβ-huPrP vs. Aβ-Aβ interactions);…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have developed the all-D-enantiomeric peptide D3, which specifically eliminates neurotoxic Aβ oligomers in vitro (Brener et al, 2015;Funke and Willbold, 2012), has a high oral bioavailability (Jiang et al, 2015) and is therapeutically active in vivo (van Groen et al, 2012;van Groen et al, 2013;van Groen et al, 2008) even after oral administration (Funke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This lead compound consists of 12 amino acid residues each in D-enantiomeric configuration. In vitro assays revealed that D3 specifically eliminates Aβ oligomers (Brener et al, 2015;Funke and Willbold, 2012), which are supposed to be the most toxic Aβ species (Benilova et al, 2012;DaRocha-Souto et al, 2011;Lambert et al, 1998;Walsh et al, 2002). In studies with AD transgenic mice, D3 reduced the Aβ plaque load as well as cerebral inflammation and showed an improvement in cognition (van Groen et al, 2012;van Groen et al, 2013;van Groen et al, 2008) even after oral administration (Funke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, investigation of changes in the expression of several presynaptic and postsynaptic proteins in primary neurons treated with a low-molecular weight and high-molecular weight b-amyloid oligomers, revealed that both oligomers significantly reduced expression of several pre synaptic proteins, including synapsin [11]. Since strong evidence exists for a central role of b-amyloid oligomers in the pathogenesis of Alzheimer's disease [3], changes in synapsin I levels observed in this disease seems to be specific response for pathological events triggered by presence of b-amyloid oligomers. As a specific change within viable nerve endings is treated also the decrease of synapsin Ib in nerve endings associated with HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%